ATIVIDADES DE AVENTURA: PRÁTICA PARA UM TEMPO LIVRE PARA O CONSUMO OU PARA UM TEMPO LIVRE MAIS HUMANO? - Verónica Gabriela Silva Piovani (Universidade Estadual do Oeste do Paraná, 2013)
This study aims to analyze the possibilities that adventure activities offer to form the human being above the use of time released by society. In this sense, the risk present in adventure activities appears as an educational element of individual and the contact with nature as a possibility for educating more autonomous individuals. Linked to these ideas, it is proposed a conception of spare time and recreation, which advocates something more than consumption and entertainment. It is understood that human being must access to a spare time where is increasingly subject to its own conditioning and not what society allows or does not allow it to do. Thus, it is concluded that adventure activities would provide the appropriate space to generate interventions for a more human spare time in the leisure area.